PARNASIANISME DALAM SYAIR NIZAR QABBANI - Rohmah, Roisah Fathiyatur (Universitas Islam Negeri Sumatera Utara Medan, 2024)
This research aims to examine whether Nizar Qabbani in creating poetry adheres to Parnasianism or not. Nizar Qabbani is a Syrian poet who wrote poetry about women. Most of Nizar Qabbani's poetry collections refer to women's bodies as objects of love. Parnasianism is a literary movement that emphasizes beauty rather than moral aspects. This research uses a descriptive analysis method by analyzing three poems by Nizar Qabbani entitled قالت لي السمراء, طفولة نهد and 100 رسالة الحب. Based on the three poems by Nizar Qabbani, they fall into the category of poems that follow the flow of Parnasianism. The poem is about women, a man's love for a woman, using beautiful language, wazan and qafiyah and not caring about the meaning it contains whether it deviates from social or religious norms.